• Matéria: Matemática
  • Autor: bailarinaraiane
  • Perguntado 7 anos atrás

b. 10y - 5 (1+ y) = 3 (2Y-2)-20​

Respostas

respondido por: JulioPlech
1

Resposta:

S = {21}

Explicação passo-a-passo:

10y - 5(1 + y) = 3(2y - 2) - 20 \\ 10y - 5 - 5y = 6y - 6 - 20 \\ 10y - 5y - 6y =  - 6 - 20 + 5 \\ -y =  - 21 \\ y = 21

respondido por: Anônimo
1

Resposta:

y = 21

Explicação passo-a-passo:

B.

10y - 5.(1+ y) = 3.(2Y-2) -20

10y - 5 - 5y = 6y - 6 - 20

5y - 5 = 6y - 26

- 5 + 26 = 6y - 5y

21 = y

y = 21

Perguntas similares